Efforts to Implement Rice Subsidy Distribution for Economically Underprivileged People in Kulon Progo - Vicki Dwi Purnomo; Kelik Endro Suryono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The distribution of rice subsidies for low-income communities has experienced many problems, so this research attempts to examine the implementation of rice subsidies for low-income communities in Kulon Progo Regency, the obstacles and efforts to overcome them. The methods used include types of sociological juridical research and analytical descriptive research specifications. The results of the study show that the implementation of rice subsidies for people's income still faces many obstacles. includes 5 namely: First, the difficulty of determining the criteria for the level of poverty, in this case, can be attempted by conducting periodic data collection, secondly, the amount of rice and beneficiaries is not the same, this can be attempted by forming special officers in receiving the distribution and weighing of raskin, thirdly the price of rice is expensive, this can be attempted by in accordance with the provisions of the law, the fourth is the delay in distribution, this can be attempted with simultaneous coordination by officials giving, distributing and receiving, fifth the quality of rice is low, this can be attempted by mixing subsidized rice with rice on the market.